Involvement of a Heptad Repeat in the Carboxyl Terminus of the Dihydropyridine Receptor β1a Subunit in the Mechanism of Excitation-Contraction Coupling in Skeletal Muscle - Sheridan, David C. (Biophysical Society, 2004)
Chimeras consisting of the homologous skeletal dihydropyridine receptor (DHPR) β1a subunit and the heterologous cardiac/brain β2a subunit were used to determine which regions of β1a were responsible for the skeletal-type excitation-contraction (EC) coupling phenotype. Chimeras were transiently transfected in β1 knockout myotubes and then voltage-clamped with simultaneous measurement of confocal fluo-4 fluorescence. All chimeras expressed a similar density of DHPR charge movements, indicating that the membrane density of DHPR voltage sensors was not a confounding factor in these studies. The data indicates that a β1a-specific domain present in the carboxyl terminus, namely the D5 region comprising the last 47 residues (β1a 478–524), is essential for expression of skeletal-type EC coupling. Furthermore, the location of β1aD5 immediately downstream from conserved domain D4 is also critical. In contrast, chimeras in which β1aD5 was swapped by the D5 region of β2a expressed Ca(2+) transients triggered by the Ca(2+) current, or none at all. A hydrophobic heptad repeat is present in domain D5 of β1a (L478, V485, V492). To determine the role of this motif, residues in the heptad repeat were mutated to alanines. The triple mutant β1a(L478A/V485A/V492A) recovered weak skeletal-type EC coupling (ΔF/F(max) = 0.4 ± 0.1 vs. 2.7 ± 0.5 for wild-type β1a). However, a triple mutant with alanine substitutions at positions out of phase with the heptad repeat, β1a(S481A/L488A/S495A), was normal (ΔF/F(max) = 2.1 ± 0.4). In summary, the presence of the β1a-specific D5 domain, in its correct position after conserved domain D4, is essential for skeletal-type EC coupling. Furthermore, a heptad repeat in β1aD5 controls the EC coupling activity. The carboxyl terminal heptad repeat of β1a might be involved in protein-protein interactions with ryanodine receptor type 1 required for DHPR to ryanodine receptor type 1 signal transmission.